Determinants and influence of wives' sex role orientation in urban family purchase decision making in Malaysia - Md Sidin, Samsinar; Zawawi, Dahlia; Teo, Carol Boon Chui (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
Changes in the socio-cultural environment such as emergence of women with dual careers entail that dimensions of their influence in family purchase decision making (FDM) be investigated in a specific context. Malaysian society differs from the West in terms of family composition and structure, values, norms, and behaviour, which affect the role that working and nonworking wives play in FDM. This study investigates factors that determine sex role orientation (SRO) of women and its influence on FDM. The methodology used a survey with structured questionnaires on a sample of 1252 working and non-working wives throughout Malaysia. Quota sampling was used to ensure representativeness of Malaysian household’s social diversity. Findings reveal that FDM is governed by SRO based on socioeconomic and cultural factors. Wives’ SRO influences major purchases of products and services that are bought for the family’s consumptions.